PENGARUH MOTIVASI, PERSEPSI KUALITAS, DAN SIKAP KONSUMEN PADA PERILAKU PEMBELIAN ULANG - Maruto, Danghyang Reksa; Artha Kusuma, A.A.G Agung; Kerti Yasa, Ni Nyoman (E-Jurnal Manajemen; Vol 4 No 8 (2015), 2015)
ABSTRACT This study aims to determine the dynamics of consumer behavior shown in repurchase behavior that is influenced by motivation, quality perception, and attitudes of consumers. The object of this research is a business of food outlet named Mie Setan Kober Bali. This research was conducted in the Denpasar city where the outlet of Mie Setan Kober Bali located. The samples used were 105 of respondents using cross-section data. The data collection technique using purposive sampling through questionnaires given directly. Source of data used are primary data and secondary data. The data collected were processed using multiple Linear Regression Analysis techniques. Results showed simultaneously three of independent variables (consumer motivation, perceived quality, and consumer attitudes) have a significant effect on the repurchase behavior in Mie Setan Kober Bali. However, partial test showed that consumer attitudes variables not significantly affect the dependent variable; a repurchase behavior.
Keywords: consumer behavior, consumer motivation, perceived quality, consumer attitude, repurchase behavior